PENGENALAN DAN PELATIHAN SOFTWARE PENGOLAHAN DATA SPSS DAN SMARTPLS DI UNIVERSITAS MIKROSKIL - Perangin-Angin, Naca; Lubis, Tya Wildana Hapsari (Universitas Methodist Indonesia, 2023)
One of the popular tools for data processing is the Statistical Package for the Social Sciences (SPSS) and Structural Equation Modeling (SEM) with SmartPLS. Understanding data processing has a very important role in preparing the final assignment. Data processing is a critical step in scientific research methodology. Students who compose their final assignment need to know and understand the techniques, stages and interpretation of results correctly so that their research has a strong basis. So the aim of Community Service Activities is to provide knowledge and understanding to final semester students who have started preparing their final assignments at Mikroskil University. Provide practical understanding and skills to students in using SPSS and SmartPLS as data processing tools. This training was carried out directly using SPSS and SMArtPLS software. Based on the results of the answers to the pre-test and post-test questions of the training participants, it can be seen that there is an increase in understanding in the introduction and use of SPSS and SmartPLS software before and after, for details, see Figure 7 for a comparison of the pre-test and post-test results. So it can be concluded that the introduction and training of SPSS and SmartPLS data processing software at Mikroskil University was successful.